Artificial Intelligence Governance in Arabic Language Education: Developing a Sustainable Learning Management Framework - Wiwik Prasetiyo Ningsih; Qur’ani Parang Wilwadikta; Jiddah Hassan Muhammad (Al-Abshar: Journal of Islamic Education Management, 2025)
The rapid integration of Artificial Intelligence (AI) into education has transformed Arabic language teaching by enabling adaptive learning, intelligent assessment, automated feedback, and personalized instructional support. Despite these advancements, the adoption of AI in Arabic language education remains largely technology-oriented, while limited attention has been given to governance mechanisms that ensure ethical, transparent, and sustainable implementation. This study aims to develop a Sustainable Learning Management Framework grounded in Artificial Intelligence Governance to support effective and responsible Arabic language education. The research employed a qualitative approach using a library research method. Data were collected from recent scholarly publications, international policy documents, and reputable databases, including Scopus, Web of Science, ScienceDirect, SpringerLink, ERIC, and Google Scholar. The collected literature was analyzed using thematic analysis and qualitative content synthesis to identify recurring governance dimensions and construct an integrated conceptual framework. The findings reveal that sustainable AI implementation depends not merely on technological sophistication but on the integration of five interconnected governance dimensions: institutional governance, ethical governance, educational data management, digital competency development, and AI-supported sustainable assessment. A notable finding indicates that institutional governance, rather than technological capability, constitutes the primary determinant of sustainable AI adoption in Arabic language education. This study contributes by proposing an integrated governance-based learning management framework that bridges AI governance, educational sustainability, and Arabic language pedagogy, providing a theoretical foundation for future education.